Nano reinforced phase-containing cement-based material matrix flexibilizer and preparation method thereof
By introducing nano-reinforced phase matrix toughening agent into cement-based materials, a stable three-dimensional network structure is formed, which solves the problem of low toughening efficiency of cement-based materials in the prior art, significantly improves the toughness and crack resistance of the material, and optimizes the microstructure and mechanical properties.
Patent Information
- Application Number
- CN202411599508.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
AI Technical Summary
The toughening technology of existing cement-based materials has problems such as low efficiency and failure to significantly improve the intrinsic toughness and crack resistance of materials, making it difficult to meet the needs of high-performance concrete materials.
The cement-based material matrix toughening agent containing nano-reinforced phase is used. The formulation includes whiskers, low-molecular-weight monomer compounds, initiators, dispersants, nano-reinforced phases and curing agents. The nanomaterial is uniformly dispersed by ultrasonic treatment or high-speed stirring to form a stable three-dimensional network structure to enhance the toughness and crack resistance of the material.
It significantly improves the toughness and crack resistance of cement-based materials, optimizes the microstructure of the material, improves the dispersion and compatibility of toughener, enhances the bonding force between polymer and cement matrix, and significantly improves the overall mechanical properties of composite materials.
Smart Images

Figure CN119528474A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, and in particular to a cement-based material matrix toughening agent containing a nano-reinforcement phase and a preparation method thereof. Background Art
[0002] In order to prevent cracks in cement-based materials (such as concrete), effective toughening and crack-resistance measures must be taken. Cracks not only seriously affect the appearance of the structure, but more importantly, they weaken the integrity and continuity of the material, which in turn has an adverse effect on the bearing capacity and durability of the structure. Cracks often become channels for harmful media such as water, oxygen, and chemicals to enter, accelerating deterioration phenomena such as steel corrosion and concrete carbonization, ultimately leading to a decline in structural performance and even endangering the safety of the building. Therefore, preventing and controlling the occurrence of cracks is the key to ensuring the long-term stability and safe use of cement-based material structures.
[0003] The toughening and crack resistance strategies of cement-based materials mainly include fiber reinforcement and matrix toughening: Fiber reinforcement: For example, fiber-reinforced materials such as ECC (engineered cement composites) and high-ductility concrete. The introduction of fibers can delay the expansion of concrete cracks to a certain extent, but its effect on suppressing initial cracks in the linear elastic stage is limited, mainly relying on physical bridging, which is a non-intrinsic toughening. Although this method improves the crack ductility of the material, its effect often depends on the mechanical force between the fiber and the matrix.
[0004] Matrix toughening: The conventional toughening method is to add polymers to the cement matrix, such as polymer mortar. Conventional polymers enhance the overall performance of the material by enhancing adhesion, improving crack resistance and improving construction performance. The polymer component in polymer mortar is usually latex powder, such as acrylate, polyvinyl alcohol and styrene-acrylate. This type of polymer forms a continuous membrane structure during the cement hydration reaction, has a certain plastic deformation ability, and can improve the flexural strength and fracture energy of the material. However, this method has a low efficiency and fails to significantly improve the intrinsic toughness of the material.
[0005] At present, a new matrix toughening technology is needed. In view of the limitations of traditional toughening methods, the structure and properties of cement hydration products can be finely controlled at the molecular, nano and micro levels to improve the intrinsic toughness and crack resistance of the cement matrix to meet the needs of high-performance concrete materials. Based on this, it is very meaningful to develop a new cement-based material matrix toughening technology. Summary of the invention
[0006] In view of the above problems, the present invention provides a cement-based material matrix toughening agent containing a nano-reinforced phase and a preparation method thereof.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The invention provides a cement-based material matrix toughening agent containing a nano-reinforced phase. The formula and raw materials of the cement-based material matrix toughening agent containing a nano-reinforced phase include, by weight percentage, 15-60% of whiskers, 35-80% of low molecular weight monomer compounds, 1.2-3% of initiators, 0.3-1.5% of dispersants, 0.05-1% of nano-reinforced phases, and 0.05-0.5% of curing agents.
[0008] Furthermore, the whiskers are one or more of aluminum oxide whiskers, potassium titanate whiskers, aluminum borate whiskers, calcium carbonate whiskers and silicon dioxide whiskers.
[0009] Furthermore, the low molecular weight monomer compound is one or more of caprolactam, acrylamide, polystyrene, polyacrylonitrile and polyurethane.
[0010] Furthermore, the initiator is potassium persulfate, ammonium persulfate or benzoyl peroxide.
[0011] Furthermore, the dispersant is polyvinyl alcohol (PVA), sodium polyacrylate (PAAS) or polycarboxylate.
[0012] Furthermore, the nano-reinforced phase is nano-silicon oxide or nano-calcium carbonate.
[0013] Furthermore, the curing agent is N-hydroxymethyl acrylamide or diisocyanate.
[0014] The present invention also provides a method for preparing the above cement-based material matrix toughening agent formula containing a nano-reinforced phase, which specifically comprises the following steps: S1: Take all the raw materials according to weight percentage for later use; S2: preparing nanomaterial dispersion: adding the nano-reinforced phase to a portion of the low molecular weight monomer compound, using ultrasonic treatment or high-speed stirring to uniformly disperse the nano-reinforced phase to form a stable nanomaterial dispersion; S3: Preparation of matrix toughening agent: Add whiskers, remaining low molecular weight monomer compounds, initiator, dispersant and curing agent to the nanomaterial dispersion one by one, and continue stirring until all ingredients are evenly mixed to ensure that the whiskers are evenly dispersed in the mixed system.
[0015] In the present invention, low molecular weight monomer compounds act as polymer matrix, and free radical polymerization occurs under the action of initiator to form polymer chains. At the same time, curing agent promotes the curing reaction between these polymer chains to build a stable three-dimensional network structure. Whiskers, as reinforcing phase, are effectively wrapped in the polymer matrix composed of low molecular weight monomer compounds, and are tightly combined with cement-based materials through physical entanglement and chemical bonding. In addition, nano-reinforcement phase is specially added to the formula, and its high specific surface area and activity not only optimize the microstructure of the material, but also significantly improve the micromechanical properties of the material, further enhancing the overall performance of the composite material. Initiator is used to promote the in-situ polymerization reaction of monomer; polymer dispersant is used to improve the dispersibility of whiskers in the polymer matrix.
[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) Significantly improve the toughness and crack resistance of materials: By introducing nanomaterials as reinforcing phases and utilizing their physical entanglement and chemical bonding with the polymer matrix and cement hydration products, the toughness and crack resistance of cement-based materials are significantly enhanced. The large specific surface area and activity of nanomaterials, as well as the reinforcing effect of whiskers, jointly improve the overall mechanical properties of composite materials.
[0017] (2) Optimizing the microstructure of materials: The introduction of nanomaterials optimizes the microstructure of materials, improving the porosity, interface transition zone and other microscopic properties of the materials. This optimization of microstructure helps reduce stress concentration and improve the durability and stability of materials.
[0018] (3) Improving the dispersibility and compatibility of toughening agents: The nanomaterials are evenly dispersed in the monomer or solvent through ultrasonic treatment or high-speed stirring, and fully mixed with whiskers, monomers and other components to ensure the uniform distribution of the toughening agent in the cement-based material. This good dispersibility and compatibility helps to improve the toughening effect and avoid performance degradation caused by agglomeration or phase separation.
[0019] (4) Enhance the bonding force between polymer and cement matrix: During the polymerization reaction, the monomer molecules of the adsorbed nanomaterials are chemically bonded with the cement hydration products. This bonding method greatly enhances the interaction between the polymer and the cement matrix, thereby improving the overall strength and stability of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a physical picture of C30 concrete with matrix toughening agent added in Experimental Example 1 of the present invention; Figure 2 is a SEM image of a C30 reference test block concrete without adding a matrix toughening agent in Comparative Example 1 of the present invention; Figure 3: is the SEM image of C30 concrete to which a matrix toughening agent is added in Experimental Example 1 of the present invention. DETAILED DESCRIPTION
[0021] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0022] The instruments, reagents, materials, etc. involved in the following examples, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following examples, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.
[0023] Example 1 The present embodiment provides a cement-based material matrix toughening agent formula containing a nano-reinforced phase. The formula raw materials of the matrix toughening agent include, by weight percentage: whiskers (aluminum oxide whiskers) 37.92%, low molecular weight monomer compounds (caprolactam) 60.1%, initiator (potassium persulfate) 1.2%, dispersant (polyvinyl alcohol) 0.3%, nano-reinforced phase (nano-silicon oxide) 0.3%, and curing agent (N-hydroxymethyl acrylamide) 0.18%.
[0024] The preparation method of the matrix toughening agent formula specifically comprises the following steps: S1: Take all the raw materials according to weight percentage for later use; S2: preparing nanomaterial dispersion: adding the nano-reinforced phase to a portion of the low molecular weight monomer compound, and using ultrasonic treatment for 30 minutes to uniformly disperse the nano-reinforced phase in the solvent to form a stable nanomaterial dispersion; S3: Preparation of matrix toughening agent: Add whiskers, remaining low molecular weight monomer compounds, initiator, dispersant and curing agent to the nanomaterial dispersion one by one, use a mechanical stirrer, and continue stirring at an appropriate speed (500 rpm) until all ingredients are evenly mixed to ensure that the whiskers are evenly dispersed in the mixed system.
[0025] Example 2 The present embodiment provides a cement-based material matrix toughening agent formula containing a nano-reinforced phase. The raw materials of the matrix toughening agent formula include, by weight percentage: whiskers (calcium carbonate whiskers) 52.525%, low molecular weight monomer compounds (acrylamide) 45.175%, initiator (ammonium persulfate) 1.35%, dispersant (sodium polyacrylate) 0.45%, nano-reinforced phase (nano-silicon oxide) 0.225%, and curing agent (N-hydroxymethyl acrylamide) 0.275%.
[0026] The preparation method of the matrix toughening agent formula specifically comprises the following steps: S1: Take all the raw materials according to weight percentage for later use; S2: preparing nanomaterial dispersion: adding the nano-reinforced phase to a portion of the low molecular weight monomer compound, and using high-speed stirring for 1 hour to uniformly disperse the nano-reinforced phase in the solvent to form a stable nanomaterial dispersion; S3: Preparation of matrix toughening agent: Add whiskers, remaining low molecular weight monomer compounds, initiator, dispersant and curing agent to the nanomaterial dispersion one by one, use a mechanical stirrer, and continue stirring at an appropriate speed (800 rpm) until all ingredients are evenly mixed to ensure that the whiskers are evenly dispersed in the mixed system.
[0027] Example 3 The present embodiment provides a cement-based material matrix toughening agent formula containing a nano-reinforced phase. The raw materials of the matrix toughening agent formula include, by weight percentage: whiskers (silicon dioxide whiskers) 47.4%, low molecular weight monomer compounds (polyacrylonitrile) 50%, initiator (benzoyl peroxide) 2%, dispersant (polycarboxylate) 0.5%, nano-reinforced phase (nano-calcium carbonate) 0.05%, and curing agent (diisocyanate) 0.05%.
[0028] The preparation method of the matrix toughening agent formula specifically comprises the following steps: S1: Take all the raw materials according to weight percentage for later use; S2: preparing nanomaterial dispersion: adding the nano-reinforced phase to a portion of the low molecular weight monomer compound, and using high-speed stirring for 1 hour to uniformly disperse the nano-reinforced phase in the solvent to form a stable nanomaterial dispersion; S3: Preparation of matrix toughening agent: Add whiskers, remaining low molecular weight monomer compounds, initiator, dispersant and curing agent to the nanomaterial dispersion one by one, use a mechanical stirrer, and continue stirring at an appropriate speed (1000rpm) until all ingredients are evenly mixed to ensure that the whiskers are evenly dispersed in the mixed system.
[0029] Example 4 The present embodiment provides a cement-based material matrix toughening agent formula containing a nano-reinforced phase. The formula raw materials of the matrix toughening agent include, by weight percentage: whiskers (potassium titanate whiskers) 15%, low molecular weight monomer compounds (acrylamide and polyurethane, mixed in a ratio of 4:1) 80% (i.e., acrylamide 64%, polyurethane 16%), initiator (ammonium persulfate) 2%, dispersant (sodium polyacrylate) 1.5%, nano-reinforced phase (nano-calcium carbonate) 1%, and curing agent (diisocyanate) 0.5%.
[0030] The preparation method is the same as Example 3.
[0031] Example 5 The present embodiment provides a cement-based material matrix toughening agent formula containing a nano-reinforced phase. The formula raw materials of the matrix toughening agent include, by weight percentage: 60% whiskers (48% aluminum borate whiskers, 12% silica whiskers), 35% low molecular weight monomer compounds (polystyrene), 3% initiator (benzoyl peroxide), 1% dispersant (polycarboxylate), 0.5% nano-reinforced phase (nano-silica), and 0.5% curing agent (N-hydroxymethyl acrylamide).
[0032] The preparation method is the same as Example 3.
[0033] Comparative Example 1 Preparation of C30 benchmark test block concrete: According to the standard of "Ordinary Concrete Mix Design Code" JGJ55-2011, the C30 concrete was tested and applied to the benchmark test block. The preparation method of C30 benchmark test block concrete is as follows: the cement is 42.5 grade ordinary Portland cement, the fine aggregate is natural sand with a particle size of less than 2.5mm, the coarse aggregate is crushed stone with a particle size of 8-12mm, the fly ash is F-Ⅱ grade fly ash and the amount of polycarboxylic acid high-performance water reducing agent is 0.2%. During the preparation process, the design slump of the concrete was set to 180mm, and the final C30 concrete mix ratio was determined as follows: cement 271kg / m 3 , fly ash 116kg / m 3 , water 178kg / m 3 , sand 636kg / m 3 , crushed stone 1181kg / m 3 , and polycarboxylic acid high performance water reducing agent 0.774kg / m 3 According to the "Ordinary Concrete Mix Design Code" JGJ55-2011, the water-cement ratio of the concrete is 0.46, the fly ash content accounts for 30% of the total cementitious material, and the sand rate and aggregate ratio is 0.35.
[0034] Experimental Example 1 On the basis of the benchmark test block of Comparative Example 1, 7.74 kg / m 3 The matrix toughening agent prepared in Example 1 (the addition amount is equivalent to 2% of the total weight of the cement-based material) is used to make C30 concrete containing a cement-based material matrix toughening agent containing a nano-reinforced phase, as shown in the attached figure. Figure 1 shown.
[0035] The preparation steps are as follows: a. Preparation of cement-based mixture: The matrix toughening agent prepared in Example 1 above is mixed with an appropriate amount of cement-based materials (such as cement, sand, water, etc.) in proportion, and a uniform cement-based mixture containing a toughening agent precursor is formed by sufficient mechanical stirring; b. Initiate polymerization reaction: add an appropriate amount of initiator to the uniformly mixed cement-based mixture, and adjust the temperature, humidity and other conditions of the reaction system to the most suitable range (temperature controlled at 20-30°C, moderate humidity) to promote the free radical polymerization reaction of the monomers of the adsorbed nanomaterials inside the cement-based material; in this process, the monomer molecules of the adsorbed nanomaterials will gradually polymerize into polymer chains and interact with the cement hydration products; c. Curing and curing: After the polymerization reaction is basically completed, the cement-based material is properly cured and maintained at a certain temperature and humidity (humidity not less than 90% at room temperature) to promote the chemical bonding between the polymer chain and the cement hydration product. After a certain period of curing (7 to 28 days), the polymer chain will be firmly combined in the cement matrix to form a reinforced and toughened cement-based material with excellent toughness and crack resistance.
[0036] Experimental Example 2 On the basis of the benchmark test block of Comparative Example 1, 7.74 kg / m 3 The matrix toughening agent prepared in Example 2 (the addition amount is equivalent to 2% of the total weight of the cement-based material) is used to make C30 concrete containing a cement-based material matrix toughening agent with a nano-reinforced phase.
[0037] The preparation method is the same as that of Experimental Example 1.
[0038] Experimental Example 3 On the basis of the benchmark test block of Comparative Example 1, 7.74 kg / m 3 The matrix toughening agent prepared in Example 3 (the addition amount is equivalent to 2% of the total weight of the cement-based material) is used to make C30 concrete containing a cement-based material matrix toughening agent with a nano-reinforced phase.
[0039] The preparation method is the same as that of Experimental Example 1.
[0040] Experimental Example 4 On the basis of the benchmark test block of Comparative Example 1, 7.74 kg / m 3 The matrix toughening agent prepared in Example 4 (the addition amount is equivalent to 2% of the total weight of the cement-based material) is used to make C30 concrete containing a cement-based material matrix toughening agent with a nano-reinforced phase.
[0041] The preparation method is the same as that of Experimental Example 1.
[0042] Experimental Example 5 On the basis of the benchmark test block of comparative example 1, 7.74 kg / m3 of the matrix toughening agent prepared in Example 5 was added (the added amount was equivalent to 2% of the total weight of the cement-based material) to prepare C30 concrete containing a cement-based material matrix toughening agent with a nano-reinforced phase.
[0043] The preparation method is the same as that of Experimental Example 1.
[0044] 1. The mechanical properties of the benchmark test block prepared in Comparative Example 1 and the C30 concrete containing the cement-based material matrix toughening agent containing the nano-reinforced phase prepared in Experimental Examples 1-5 were tested. The test indicators are shown in Table 1, and the test results are shown in Table 2.
[0045] Table 1 Test indicators
[0046] Table 2 Mechanical properties test results
[0047] It can be seen from the results in Table 2 that the C30 concrete of Experimental Examples 1-5 all showed significant advantages over the benchmark test blocks. Specifically, the 28-day compressive strength of Experimental Example 1 was 1.8 MPa higher than that of the benchmark test block, and the splitting tensile strength and flexural strength were also improved. Although the slump was slightly reduced, the optimization of the overall mechanical properties showed that its structure was more solid. Experimental Example 2 was even more outstanding. Not only did it reach the highest compressive strength of 36.2 MPa, which was 3.5 MPa higher than the benchmark test block, but it also performed well in splitting tensile strength and flexural strength, showing excellent mechanical performance improvement. Although the compressive strength of Experimental Example 3 was slightly lower than that of Experimental Example 2, it was still higher than the benchmark test block, and its flexural strength reached the highest 5.0 MPa, and the splitting tensile strength was also maintained at a high level. At the same time, the reduction in slump may mean that its working performance is more stable, which is conducive to construction control. In summary, Experimental Examples 1-5 are superior to the benchmark test blocks in terms of mechanical properties, demonstrating that the addition of cement-based material matrix toughening agents containing nano-reinforced phases effectively improves the performance of cement-based materials.
[0048] 2. In order to further explore the improvement effect of matrix toughening agent on concrete microstructure, the advanced German Zeiss Sigma 300 high-performance electron microscope was used to characterize the microstructure of C30 benchmark concrete without matrix toughening agent (Comparative Example 1) and C30 concrete with matrix toughening agent (Experimental Example 1). The results are as follows: Figure 2 The scanning electron microscope (SEM) image of the C30 reference concrete block without adding matrix toughening agent in Comparative Example 1 is shown. Figure 3The SEM image of C30 concrete with matrix toughening agent added in Experimental Example 1 is shown. Through detailed scanning electron microscopy observation, it was found that the overall hydration microstructure of concrete became significantly denser after adding matrix toughening agent. The matrix toughening agent formed a close intercalation with calcium sulfonate in the CSH gel product to build a network structure. This change optimized the microstructure of cement-based materials. In addition, the addition of matrix toughening agent also led to a decrease in pore size, which further confirmed that the matrix toughening agent effectively played a role in filling voids and improving structural density in the cement matrix.
[0049] In summary, the present invention creatively introduces nanomaterials into the matrix toughening agent. These nanomaterials, with their excellent high specific surface area and highly active characteristics, greatly enhance the effectiveness of the toughening agent through the dual synergistic effect of physical entanglement and chemical bonding. Nanomaterials are embedded in whiskers as reinforcing phases and undergo polymerization reactions with low molecular weight monomer compounds, ultimately forming a unique polymer chain network structure that can be tightly chemically bonded to cement hydration products. This structure not only significantly enhances the toughness and crack resistance of cement-based materials, but also optimizes the pore structure of concrete at a microscopic level and reduces voids. Nanomaterials can effectively control the aggregation tendency of polymer particles during the polymerization reaction to prevent them from aggregating into large particles or clumps due to mutual attraction, thereby stabilizing the uniformity of the polymerization reaction. This technological innovation of the present invention has successfully broken through the efficiency limitations of traditional toughening methods, demonstrating its forward-looking technological innovation and huge market application potential.
[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A cement-based material matrix toughening agent containing a nano-reinforced phase, characterized in that: The formula and raw materials of the cement-based material matrix toughening agent containing nano-reinforced phase include, by weight percentage: 15-60% whisker, 35-80% low molecular weight monomer compound, 1.2-3% initiator, 0.3-1.5% dispersant, 0.05-1% nano-reinforced phase, and 0.05-0.5% curing agent.
2. The cement-based material matrix toughening agent containing a nano-reinforced phase according to claim 1, characterized in that: The whiskers are one or more of aluminum oxide whiskers, potassium titanate whiskers, aluminum borate whiskers, calcium carbonate whiskers and silicon dioxide whiskers.
3. The cement-based material matrix toughening agent containing a nano-reinforced phase according to claim 1, characterized in that: The low molecular weight monomer compound is one or more of caprolactam, acrylamide, polystyrene, polyacrylonitrile and polyurethane.
4. The cement-based material matrix toughening agent containing nano-reinforced phase according to claim 1, characterized in that: The initiator is potassium persulfate, ammonium persulfate or benzoyl peroxide.
5. The cement-based material matrix toughening agent containing a nano-reinforced phase according to claim 1, characterized in that: The dispersant is polyvinyl alcohol, sodium polyacrylate or polycarboxylate.
6. The cement-based material matrix toughening agent containing nano-reinforced phase according to claim 1, characterized in that: The nano-reinforced phase is nano-silicon oxide or nano-calcium carbonate.
7. The cement-based material matrix toughening agent containing nano-reinforced phase according to claim 1, characterized in that: The curing agent is N-hydroxymethyl acrylamide or diisocyanate.
8. A method for preparing a cement-based material matrix toughening agent containing a nano-reinforced phase as claimed in any one of claims 1 to 7, characterized in that: The specific steps include: S1: Take all the raw materials according to weight percentage for later use; S2: preparing nanomaterial dispersion: adding the nano-reinforced phase to a portion of the low molecular weight monomer compound, using ultrasonic treatment or high-speed stirring to uniformly disperse the nano-reinforced phase to form a stable nanomaterial dispersion; S3: Preparation of matrix toughening agent: Add whiskers, remaining low molecular weight monomer compounds, initiator, dispersant and curing agent to the nanomaterial dispersion one by one, and continue stirring until all ingredients are evenly mixed to ensure that the whiskers are evenly dispersed in the mixed system.